Market and state in socio-economic order: a brief review of theories - Anna E. Jurczuk; Piotr Pysz (Institute of Economic Research (IER), 2018)
The purpose of this paper is to present the views of various schools of economic thought on the sources of the institutional order of economies. The premises of the theories of constituted and spontaneous economic orders are taken as the criteria on the basis of which the sources of an institutional order are identified. In order to meet the research objectives, the paper present, on the basis of the theoretical notions of constituted and spontaneous economic orders, the views on the sources of institutional order in capitalism within the last 250 years, i.e. from the times of Adam Smith until the present day. Main results indicate that, the classical/neoclassical model of economic order, interpreted here as the ideal one, is arise by itself as a result of market interaction. In contradistinction to the above ultraliberal model of economic order is the consistently centralised model deriving from the Marxist tradition. A synthesis of the strictly liberal and the centralised models is the ordoliberal model of economic order. As regards the course of market interactions and the auto-formation of spontaneous rules of an economic order resulting from the market operations, it is a par exellence liberal concept. On the other hand, from the consistently centralised model it borrows the idea of top-down dictation of economic order principles by the political government. This synthesis constitutes ordoliberalism and implies a feedback between the constituted and spontaneous rules of economic order.
Keywords: B1; B5; 330; classical economics; Marxism; ordoliberalism; economic order; institutional analysis